ANALISIS KINERJA PENGELOLAAN KEUANGAN DESA DENGAN PENDEKATAN PERATURAN MENTERI DALAM NEGERI REPUBLIK INDONESIA NOMOR 73 TAHUN 2020 DI KECAMATAN ANAK RATU AJI KABUPATEN LAMPUNG TENGAH - Nico Finandi Asnawi; Bambang Suhada; Muhammad Ihsan Dacholfany (SIMPLEX: Journal of Economic Management, 2021)
The purpose of this study was to determine and analyze the performance of village financial management, constraints, and solutions given in Anak Ratu Aji District, Central Lampung Regency. The objects of this research are six (6) villages studied, namely Gedung Sari, Karang Jawa, Bandar Putih Tua, Ratu Building, Suka Jaya, and Sri Mulyo villages. The research method used is quantitative. The results showed that there were six (6) villages studied, namely Gedung Sari, Karang Jawa, Bandar Putih Tua, Ratu Building, Suka Jaya, and Sri Mulyo villages. Of the six villages, five of them have the village's financial management performance in the good category/criteria, so that it must be maintained and even improved to be very good, only Gedung Ratu village is in the sufficient criteria, so it must be improved to be good like other villages, it can even be improved to very good. Obstacles in managing village finances in Anak Ratu Aji Subdistrict, Central Lampung Regency, include The absence of regulations for setting village government accounting standards and the absence of regulations for the implementation and development of village apparatuses that are complete, up-to-date, and by higher regulations. Supervision has not fully covered the evaluation of the suitability of the Village Budget with the priority scale for the use of Village Funds, and the follow-up improvements have not been included in the supervisory results report. Many village officials do not understand the rules/stipulations for managing the Village Fund. So far, Design & RAB as well as other documents have been prepared from scratch. Community participation is still minimal. Solutions that can be provided include: There is a need for regulation of village government accounting standards and the absence of regulations for the implementation and development of village apparatuses that are complete, up-to-date, and following higher regulations. Villages are becoming more participatory, transparent, and accountable. There should be no conflict between institutions in the village. Community participation in supervising the management of village funds must be increased.